1994
DOI: 10.1590/s0074-02761994000100013
|View full text |Cite
|
Sign up to set email alerts
|

Sialoglycoconjugates in Trypanosoma cruzi-host cell interaction: possible biological model - a review

Abstract: A number of glycoconjugates, including glycolipids and glycoproteins, participate in the process of host-cell invasion by Trypanosoma cruzi and one of the most important carbohydrates involved on this interaction is sialic acid. It is known that parasite trans-sialidase participates with sialic acid in a coordinated fashion in the initial stages of invasion. Given the importance of these sialoglycoconjugates, this review sets out various possible biological models for the interaction between the parasite and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Although parasites generally cannot transfer sialic acid to their glycoproteins from CMP-sialic acid, sialic acid is an important ligand for trypanosomes on the host cell surface [Vermelho and Meirelles, 1994]. Epimastigotes and trypomastigotes of Trypanosoma cruzi contain a surface trans-sialidase that utilizes host cell surface α2-3-linked sialic acid as a substrate to sialylate their own glycoproteins [Schenkman et al, 1993;Takahashi et al, 1995].…”
Section: Parasitic Infectionsmentioning
confidence: 99%
“…Although parasites generally cannot transfer sialic acid to their glycoproteins from CMP-sialic acid, sialic acid is an important ligand for trypanosomes on the host cell surface [Vermelho and Meirelles, 1994]. Epimastigotes and trypomastigotes of Trypanosoma cruzi contain a surface trans-sialidase that utilizes host cell surface α2-3-linked sialic acid as a substrate to sialylate their own glycoproteins [Schenkman et al, 1993;Takahashi et al, 1995].…”
Section: Parasitic Infectionsmentioning
confidence: 99%
“…Culture-derived metacyclic forms had decreased their capacity to invade cells and whenever becoming intracellular were destroyed inside phagolysosomes (Contreras et al 1994). There is increasing evidence that the entry of T. cruzi invasive forms into mammalian cells involves glycoconjugates-dependent attachment followed by parasite internalization (Andrews et al 1984, Yoshida et al 1990, 1997, Schenkman et al 1993, Ramirez et al 1993, Vermelho & Meirelles 1994, Burleigh & Andrews 1995. The glycoconjugates, including glycolips and glycoproteins may therefore play a role important in the virulence of the parasites.…”
mentioning
confidence: 99%
“…It has been described that during the formation of the PV some host cell plasma membrane components will be part of the membrane of the PV, but other components will not be found in the membrane which lines the PV. The involvement of glycoconjugates in this invasion have shown that a number of carbohydrates -such as galactose, N-acetyl galactosamine, Nacetyl glucosamine, mannose and sialic acid -components of glycoproteins and glycolipids present on the surface of both parasite and/or host cell may participate in the interaction process (Andrews & Coli 1981, Crane & Dvorak 1982, Vilalta & Kierzenbaum 1983, Zingales & Coli 1985, Meirelles et al 1986, Piras et al 1987, Ouassi 1988, Vermelho et al 1992, Barbosa & Meirelles 1992, Schenkman & Eichinger 1993, Vermelho & Meirelles 1994, Soeiro et al 1995. Mannosyl residues and their counter-receptors play an important role during the interaction of T. cruzi and host cells.…”
Section: Cardiomyocytes (Cm) Are the Main Targets Formentioning
confidence: 99%